A trnI_CAU Triplication Event in the Complete Chloroplast Genome of Paris verticillata M.Bieb. (Melanthiaceae, Liliales) - Do, Hoang Dang Khoa (Oxford University Press, 2014)
The chloroplast is an essential plant organelle responsible for photosynthesis. Gene duplication, relocation, and loss in the chloroplast genome (cpDNA) are useful for exploring the evolution and phylogeny of plant species. In this study, the complete chloroplast genome of Paris verticillata was sequenced using the 454 sequencing system and Sanger sequencing method to trace the evolutionary pattern in the tribe Parideae of the family Melanthiaceae (Liliales). The circular double-stranded cpDNA of P. verticillata (157,379 bp) consists of two inverted repeat regions each of 28,373 bp, a large single copy of 82,726 bp, and a small single copy of 17,907 bp. Gene content and order are generally similar to the previously reported cpDNA sequences within the order Liliales. However, we found that trnI_CAU was triplicated in P. verticillata. In addition, cemA is suspected to be a pseudogene due to the presence of internal stop codons created by poly(A) insertion and single small CA repeats. Such changes were not found in previously examined cpDNAs of the Melanthiaceae or other families of the Liliales, suggesting that such features are unique to the tribe Parideae of Melanthiaceae. The characteristics of P. verticillata cpDNA will provide useful information for uncovering the evolution within Paris and for further research of plastid genome evolution and phylogenetic studies in Liliales.